Calculation of 2-temperature plasma thermo-physical properties considering condensed phases: application to CO2–CH4 plasma: part 1. Composition and thermodynamic properties. (13th September 2016) - Wu, Yi; Chen, Zhexin; Rong, Mingzhe; Cressault, Yann; Yang, Fei; Niu, Chunping; Sun, Hao
Abstract: As the first part of this series of papers, a new calculation method for composition and thermodynamic properties of 2-temperature plasma considering condensed species under local chemical equilibrium (LCE) and local phase equilibrium assumption is presented. The 2-T mass action law and chemical potential are used to determine the composition of multiphase system. The thermo-physical properties of CO2 –CH4 mixture, which may be a possible substitution for SF6, are calculated by this method as an example. The influence of condensed graphite, non-LTE effect, mixture ratio and pressure on the thermo-physical properties has been discussed. The results will serve as reliable reference data for computational simulation of CO2 –CH4 plasmas.